A general model for rectangular footings part I: optimal surface - Marylú García-Galván; Arnulfo Luévanos Rojas; Sandra López-Chavarría; Manuel Medina-Elizondo; José Benito Rivera-Mendoza (Dyna, 2022)
This paper shows a general model of rectangular footings to obtain the soil minimum contact area (optimal surface) that support from 1 to n columns aligned on a longitudinal axis. The proposed model considers that the soil pressure varies linearly. The recently published models have been presented individually to obtain the soil contact area for rectangular isolated footings, rectangular combined footings that support two columns, these models present the equations, but it is not guaranteed to be the minimum area. The present research complies with the models mentioned above and can be applied to footings that support 3 or more columns, and also the minimum area is guaranteed. Also, numerical problems are shown the soil minimum contact surface for rectangular isolated footings, and rectangular combined footings that support two and three columns (unrestricted on its sides, one side restricted and two opposite sides restricted).